2017
DOI: 10.1038/srep43027
|View full text |Cite
|
Sign up to set email alerts
|

The miRNAome of Catharanthus roseus: identification, expression analysis, and potential roles of microRNAs in regulation of terpenoid indole alkaloid biosynthesis

Abstract: MicroRNAs (miRNAs) regulate numerous crucial biological processes in plants. However, information is limited on their involvement in the biosynthesis of specialized metabolites in plants, including Catharanthus roseus that produces a number of pharmaceutically valuable, bioactive terpenoid indole alkaloids (TIAs). Using small RNA-sequencing, we identified 181 conserved and 173 novel miRNAs (cro-miRNAs) in C. roseus seedlings. Genome-wide expression analysis revealed that a set of cro-miRNAs are differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 86 publications
(105 reference statements)
0
28
1
Order By: Relevance
“…Although we identified many JA-responsive miRNAs, only two were conserved with other plants: miR172 and miR395, which decreased and increased with JA, respectively. In contrast, others have reported several conserved, JA-responsive miRNAs (Qiu et al, 2009 ; Bozorov et al, 2012 ; Zhang et al, 2012 ; Xu et al, 2016 ; Shen et al, 2017 ). One reason for this discrepancy may be our stringent requirements for differential expression, owing to the availability of biological replicates.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although we identified many JA-responsive miRNAs, only two were conserved with other plants: miR172 and miR395, which decreased and increased with JA, respectively. In contrast, others have reported several conserved, JA-responsive miRNAs (Qiu et al, 2009 ; Bozorov et al, 2012 ; Zhang et al, 2012 ; Xu et al, 2016 ; Shen et al, 2017 ). One reason for this discrepancy may be our stringent requirements for differential expression, owing to the availability of biological replicates.…”
Section: Discussionmentioning
confidence: 93%
“…miRNAs have been implicated in numerous abiotic and biotic stress responses, such as those induced by temperature, salinity, drought, light, nutrient deficiencies, oxidative stress, and pathogens (reviewed in Khraiwesh et al, 2012 ; Li et al, 2017 ; Islam et al, 2018 ). Previous reports have characterized the effect of JA or its methyl ester (JA-Me) on miRNAs in Arabidopsis, Nicotiana attenuata, Taxus chinensis, Lycoris aurea , and Catharanthus roseus (Qiu et al, 2009 ; Bozorov et al, 2012 ; Zhang et al, 2012 ; Xu et al, 2016 ; Shen et al, 2017 ). Control of JA biosynthesis through miR319-targeted TCP transcription factors has also been established (Schommer et al, 2008 ; Zhao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that the expression levels of PLP_deC genes are also influenced by abiotic and biotic stresses [28][29][30]. Furthermore, plant hormones such as ABA, SA, and ethylene also modulate the expression of these genes [17,29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, miRNAs exhibit tissue or stage-specific expression patterns, and participate in the regulation of the accumulation of secondary metabolites such as steroids and ketones by negatively regulating the expression of target genes [8][9][10]. For instance, miRNAs are involved in the biosynthesis of terpenoid indole alkaloids in Catharanthus roseus [ 11]. Additionally, miR156, miR828, miR858, and miR5072 regulate anthocyanin accumulation in apple peel [ 12].…”
Section: Introductionmentioning
confidence: 99%